PENGARUH MOTIVASI BELAJAR DAN HASIL BELAJAR TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA KELAS XII SMK NEGERI 5 PEKANBARU - Sasmi, Wilda Yulia; Johan, Rina Selva; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : This study aims to determine the effect of learning motivation and learning outcomes on the interest to continue studies to college in the students of class XII SMK country 5 Pekanbaru. Population in this study is the students of class XII SMK country 5 Pekanbaruas many as 300 people, and the sample as many as 75 people. Data inquiries using questionnaires and documentation. Analysis of data used is mutiple linear regression. The result of research based on multple linear regression shows the motivation of learning and learning outcomes have an effect on the interest of continuing study to college in the students of class XII SMK country 5 Pekanbaru, this can be seen from the constant valeu (a) of 1,420, regression coeffficient value of learning motivation variable of 0,263, and value of regression coefficient of learning result variable equal to 0,390 with regression equation 1,420 + 0,263 +0,390. Seen from the calculation of R2 (R square change) obtained value of 0,296. Meaning is that the percentage of influence of learning motivaton variables and learning outcomes of interest to continue studies to college of 29,6%.Key word : Motivation to learn, Learning outcomes, Interest in continuing study to college